Microcirculation changes of bulbar conjunctiva at primary pterygium - A. V. Petrayevsky; K. S. Trishkin (Oftalʹmologiâ, 2014)
Purpose. To reveal microcirculation changes in nasal part of bulbar conjunctiva at various stages of primary pterygium formation using fluorescent angiography.Methods. 10 eyes (10 patients) with pinguecula, 15 eyes (14 patients) with primary pterygium were investigated. As a control group 10 eyes (10 patients) without pathological changes in nasal part of conjunctiva were investigated. Biomicroscopy and anterior segment fluorescent angiography were performed for all patients.Results. Severe changes of microcirculation in nasal part of conjunctiva in patients with pinguecula and pterygium were revealed in comparison with a control group. The defect of terminal limbal arcades confirmed by fluorescent angiography can be a sign of transformation of pinguecula into pterygium. Primary pterygium gets blood supply from posterior conjunctival arteries, capillary network of a semilunar fold and also from returnable branches of anterior ciliary arteries. Neovascularization going from a semilunar fold to a body of pterygium is one of possible components in pathogenesis of pterygium.Conclusion. The obtained data testify about sign of transformation of pinguecula into pterygium, blood supply sources of pterygium and a role of neogenic vessels from a capillary network of a semilunar fold in pathogenesis of this disease.